2018
DOI: 10.1111/febs.14638
|View full text |Cite
|
Sign up to set email alerts
|

p53 tumor suppressor and iron homeostasis

Abstract: Iron is an essential nutrient for all living organisms and plays a vital role in many fundamental biochemical processes, such as oxygen transport, energy metabolism, and DNA synthesis. Due to its capability to produce free radicals, iron has deleterious effects and thus, its level needs to be tightly controlled in the body. Deregulation of iron metabolism is known to cause diseases, including anemia by iron deficiency and hereditary hemochromatosis by iron overload. Interestingly, dysregulated iron metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 116 publications
0
40
0
Order By: Relevance
“…Iron is required for numerous critical processes such as DNA synthesis, heme synthesis, and iron-sulfur cluster synthesis [129, 130]. It also plays an important role in the active sites of various enzymes which are involved in the formation such as LOX, xanthine oxidase, NADPH oxidases, and mitochondrial complex I and III [131133].…”
Section: Roles Of Lipid Peroxidation In Different Cell Deathmentioning
confidence: 99%
“…Iron is required for numerous critical processes such as DNA synthesis, heme synthesis, and iron-sulfur cluster synthesis [129, 130]. It also plays an important role in the active sites of various enzymes which are involved in the formation such as LOX, xanthine oxidase, NADPH oxidases, and mitochondrial complex I and III [131133].…”
Section: Roles Of Lipid Peroxidation In Different Cell Deathmentioning
confidence: 99%
“…In contrast to other tissues or organs, such as the liver, which is the main organ for iron storage in vivo, there has been no evidence of iron deposition in normal cervical tissues and cervical lesions thus far. 23,24 Therefore, we infer that R2* has good prospects for the hypoxic detection of cervical cancer. In this study, we found that HIF-1α expression had a moderate degree of correlation with R2*, which is in line with previous research.…”
Section: Discussionmentioning
confidence: 86%
“…Usually, iron, hemosiderin, and other paramagnetic substances can affect the value of R2*. In contrast to other tissues or organs, such as the liver, which is the main organ for iron storage in vivo, there has been no evidence of iron deposition in normal cervical tissues and cervical lesions thus far . Therefore, we infer that R2* has good prospects for the hypoxic detection of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of iron on cell cycle progression extends beyond RNR as cyclinD/cyclin-dependent kinase 4 (CDK4) are degraded and protein levels are reduced by iron depletion [68,69]. Iron depletion has also been shown to increase both p53 and p21 expression, leading to increased CDK4 inhibition and cell cycle arrest [70,71]. Conversely, iron overload increases cyclin D1 expression and cell proliferation in mouse hepatocytes [1].…”
Section: Iron and Cancermentioning
confidence: 99%